Significance and diversity of landscape design in rehabilitation - Stokmane, Ilze; Graudiņa, Kitija (Landscape Architecture and Art, 2024)
The World Health Organisation defines human health as a state of complete physical, mental and social well-being and not merely the absence of disease or infirmity. Nature is one of the mechanisms that can help to achieve the aspects highlighted in this definition. Recovery environments, such as therapeutic gardens in the outdoor areas of treatment centers, play a crucial role in challenging life circumstances and can supplement traditional forms of treatment. They are not a substitute for medical care and different therapies, but rather function as a support system and enhancement for achieving quicker and higher quality outcomes. The aim of this paper is to look at the possibilities of creating different revitalisation landscapes, including abandoned ones, and to adapt them to different target groups, which are increasing in number and diversity in today’s changing political and economic situation, as well as to the growing number of people who need a specific approach to the recovery process, which can also be provided by a well-designed outdoor space. The revitalisation of the landscape of abandoned rehabilitation facilities is also essential for sustainability processes, when the functional zoning of such areas is improved and outdoor spaces that can fulfil their function in the long term are brought back to life, transformed into spaces adapted to modern needs. Based on the analysis and theoretical studies of different outdoor spaces of abandoned rehabilitation institutions, proposals and thematic models for the revitalisation of rehabilitation landscapes near abandoned water, near settlements and surrounded by forests have been prepared, highlighting the potential of such areas within individual landscapes and emphasising the importance of rehabilitation landscapes in each of them.